Antioxidant and anti-diabetic status of popular Malay health tonic consumed for wellness: help or hype? - Mohd Nazri Zayapor,; Aminah Abdullah,; Wan Aida Wan Mustapha, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Contemporary Malay health tonics labeled as botanical drinks are advertised in the Malaysian market as effective therapeutic supplements toward improving consumer health. The therapeutic claims associated with high antioxidants are based on the herbal ingredients used, yet unproven by scientific evidence. Moreover, they are mostly sweetened with sugar, which may arise the potential of diabetic risk. Thus, a dire clarification on the potential antioxidant status and diabetic risk of these products is essential to nullify over claims. Eight commercial botanical drinks that serve as health tonics were selected based on their advertisement popularity and traditional medicine sellers’ interview feedbacks. The selected tonics were mutually compared with a green tea (DGT01) as the benchmark for their total phenolic content (TPC); antioxidant activities [the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging inhibition capacities, IC50; Ferric ion reducing antioxidant power (FRAP); and Oxygen radical absorbance capacity (ORAC)], anti-diabetic property through the α-glucosidase inhibition (AGI) and as well as the sugar content. The results were mapped for variations using Principal Component Analysis (PCA). Three out of 8 health tonics (NS12, SK53, and MU13) has approximately 3 to 4-fold, 1.1-fold and 2.5-fold higher in TPC, ORAC, and FRAP reducing capacities, respectively. Only NS12 and SK53 showed strong AGI (>80% inhibition). Three tonics, NS12, SK53, and HS06 exhibited precaution levels of sugar with more than 180 mg of total sugars per serving. From the PCA, DGT01 was dissociated from any tonic. NS12 and SK23 were closely related in terms of antioxidant and AGI activities. Although they showed promising therapeutic benefits due to high antioxidant activities and low diabetic risk, the tonics’ efficacies and safety are still dubious shall be verified by reliable clinical trials. The selection of a health tonic shall not only be based on multi antioxidant-rich ingredients but low in sugar for a healthier choice.